Midwifery Care Neonatal With BPM Murtinawita Spit On Pekanbaru: Midwifery Care Neonatal With BPM Murtinawita Spit On Pekanbaru - Kiki Megasari (Journal of Midwifery and Nursing, 2020)
Spit is the most common clinical symptoms found in infants who have gastroesophageal reflux (RGE). Gastroesophageal reflux is defined as the return of gastric contents into the esophagus involuntarily without effort from the baby, while the regurgitation is the term used when the stomach contents are removed by mouth. As for the 25% of parents, especially mothers, Consider that mumbling is a worrying condition for Themselves. Although normal, excessive mumbling can cause various complications that will interfere with the growth of the baby. The general objective of this study is to be Able to perform Midwifery care in infants with spit problems through a management approach and document Midwifery Midwifery care in babies spit. According to research conducted Occurs spit up a lot at the age of 0-3 months, the frequency sometimes Reaches 1 to 4 times a day. 25% of babies experience mumbling more than 4 times a day for the first 3 months. Spit will be a pathological symptom if the frequency is more than 2 times a day for more than 2 days / week so, advice for the mother to pay more attention to the baby again if suckling position the baby to suckle properly, and to always Belch the baby after breastfeeding.